Identification of N-Hexadecanoyl-L-homoserine lactone (C16-AHL) as signal molecule in halophilic bacterium Halomonas smyrnensis AAD6 - TOKSOY ÖNER, EBRU; SÜNER, SALİM (SPRINGER, 2016)
Quorum sensing (QS) mechanisms regulate a variety of vital functions such as motility, growth inhibition, biofilm development, virulence expression and plasmid conjugation. Many of these activities are essential for the well-being of organisms, in particular in extreme conditions such as hypersaline environments. Halophiles are able to synthesize products that are stable, and to exploit their activities under such extreme conditions, namely saline environments such as marine habitat, salt lakes, brines and saline soils. The versatility of these products leads researchers to address their interest in biotechnological applications. In this study, the QS activity of Halomonas smyrnensis AAD6-a moderately halophilic and exopolysaccharide-producing bacterium-was investigated. Dichloromethane extracts from stationary phase cultures of Halomonas smyrnensis AAD6 were partially purified, and C-16-AHL was identified by LC-MS analysis. The synthesis of autoinducers was assayed and their production was detected starting from 48 h of growth. The growth-phase dependent production of exopolysaccharide (EPS) and signal molecules suggested that these activities could be linked.
Keywords: Halomonas smyrnensis; AHL; Agrobacterium tumefaciens NTL4; Quorum sensing; UPLC-MRM analysis; ACYLHOMOSERINE LACTONES; QUORUM; COMMUNICATION; ARCHAEON